THE WAY SUNDANESE GIVE NAMES TO THEIR BABY: CULTURAL ANTHROPOLOGY VIEW IN ETHNOMATHEMATICAL STUDIES - Eko Yulianto; Muhamad Zulfikar Mansyur; Iyus Jayusman; Zulpi Miftahudin (Journal of Authentic Research on Mathematics Education (JARME), 2022)
The mystery of numbers that were considered to have a role in the mystical dimension has long been practiced since the time of Pythagoras, then known as numerology. Some people in Sundanese tradition believe that numerology brings a lucky influence on their lives and generations. This study aims to reveal how the Sundanese tradition of naming their newborn babies and conduct a phenomenological study on several respondents with unique experiences related to Sundanese numerology in their names. The phenomenon experienced by respondents is seen from the point of view of cultural anthropology. This research was designed using qualitative methods through two approaches, ethnomathematics and phenomenology. Respondents were selected using purposive sampling and snowball methods and obtained 25 respondents scattered around the districts of Ciamis, Banjar, Tasikmalaya, and Garut in West Java. All respondents are expert resources as cultural practitioners in their own culture who can explain the numerology system they used, known as Kasepuhan. The results of the study show that there are many different numerological methods for calculating "lucky names" in the Sundanese tradition that depend on the epistemology of the science of Kasepuhan in their own culture. Most of the calculations involve the concept of integer (modular) operations where each ‘reminder’ represents its own philosophical meaning. Although mathematically the methods of calculating “lucky names” can be learned by everyone, the practice of these calculations is in fact only carried out by people who are considered to have been established from the aspect of science. This article discusses why the mystical phenomenon behind the numerology of the Sundanese tradition cannot be calculated arbitrarily by anyone, people trust more in the numerology calculations performed by Kasepuhan.